In vivo Confocal Microscopic Evaluation of Corneal Dendritic Cell Density and Subbasal Nerve Parameters in Dry Eye Patients: A Systematic Review and Meta-analysis - Xu, Jing; Chen, Peng; Yu, Chaoqun; Liu, Yaning; Hu, Shaohua; Di, Guohu (Frontiers in Medicine, 2021)
Purpose: To conduct a systematic review and meta-analysis of the available research on evaluating changes in corneal dendritic cell density (CDCD) and the main subbasal nerve parameters (SNPs) on the ocular surface and assessing the diagnostic performance of in vivo confocal microscopy in patients with dry eye disease. Methods: A computerized systematic review of literature published in PUBMED, EMBASE, Web of Science, Scopus, and the Cochrane Central Register of Controlled Trials until May 8, 2020 was performed. All statistical analyses were conducted in RevMan V.5.3 software. The weighted mean differences (WMDs) and standardized mean differences (SMDs) with 95% confidence intervals (CI) between dry eye patients and healthy subjects were presented as results. Results: A total of 11 studies with 755 participants were recruited, and 931 eyes were included in this meta-analysis. However, not all studies reported both CDCD and SNPs. CDCD in the central cornea was higher (WMD = 51.06, 95% CI = 39.42–62.71), while corneal nerve fiber density (CNFD) and corneal nerve fiber length (CNFL) were lower (WMD = −7.96, 95% CI = −12.12 to −3.81; SMD = −2.30, 95%CI = −3.26 to −1.35) in dry eye patients in comparison with the corresponding values in healthy controls (all p < 0.00001). Conclusion: Taken together, while CNFD and CNFL were lower in dry eye patients, central CDCD showed a significant increase in these patients in comparison with the corresponding values in healthy controls.